(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This paper examines the key financial indicators used to assess the financial stability of commercial banks. The study focuses on profitability, efficiency, and resource utilization ratios such as return on equity (ROE), return on assets (ROA), profit-to-income, profit-to-expense, asset yield, and the efficiency of using borrowed funds. These indicators serve as essential tools for evaluating a bank’s operational performance, internal financial strength, and risk exposure.